Late-Onset Isolated Growth Hormone Deficiency. Issue 2 (3rd March 2023) - Samuels, Julie G; Chimatapu, Sri Nikhita; Savage, Martin O; Rapaport, Robert
Abstract: Two male patients, who presented at 13.5 and 13.9 years of age with growth failure and short stature, were ultimately diagnosed with isolated growth hormone deficiency (GHD). Patient 1 was first evaluated when his height declined from −0.67 SD to −1.3 SD. He had a peak growth hormone (GH) concentration to GH stimulation test (GHST) of 16.9 ng/mL (16.9 μg/L) and remained untreated. As puberty advanced, his height decreased further to −1.65 SD. A second GHST while his serum testosterone was 79 ng/dL (2.74 nmol/L) had a peak GH of 5.4 ng/mL (5.4 μg/L), consistent with GHD. He was treated with GH for 4.8 years and reached adult height of 180.5 cm (0.57 SD), gaining 2.22 SDS. Patient 2, height −2.63 SD, had an unstimulated peak GH concentration of 19 ng/mL (19 μg/L). As puberty advanced, his height decreased further to −2.96 SD. Repeat peak GH concentration was 9.2 ng/mL (9.2 μg/L) when serum testosterone was 83.9 ng/dL (2.91 nmol/L). GH treatment resulted in rapid increase of height velocity from 1.8 cm/year to 11.3 cm/year in 6 months, consistent with GHD. Both patients demonstrate that GHD may develop over time and cannot be excluded by a single GHST. Longitudinal monitoring of children with poor growth as puberty progresses is essential to uncover GHD.